Highly effective ionic liquids for biodiesel production from waste vegetable oils - Fathy A. Yassin; Fathy Y. El Kady; Hoda S. Ahmed; Latifa K. Mohamed; Seham A. Shaban; Ahmed K. Elfadaly (Egyptian Journal of Petroleum)
As conventional energy sources deplete, the need for developing alternative energy resources which are environment friendly becomes more imperative. Vegetable oils are attracting increased interest in this purpose. The methanolysis of vegetable oil to produce a fatty acid methyl ester (FAME, i.e., biodiesel fuel) was catalyzed by commercial ionic liquid and its chloride modification. The imidazolium chloride ionic liquid was frequently chosen for the synthesis of biodiesel. The dual-functionalized’ ionic liquid is prepared by a direct combination reaction between imidazolium cation and various metal chlorides such as CoCl2, CuCl2, NiCl2, FeCl3 and AlCl3. Imidazolium tetrachloroferrate was proved to be a selective catalyst for the methanolysis reaction at a yield of 97% when used at 1:10, catalyst: oil ratio for 8 h at 55 °C. Operational simplicity, reusability of the used catalyst for 8 times at least, high yields and no saponification are the key features of this methodology. The dynamic viscosity and density of the upgraded vegetable oil decreased from 32.1 cP and 0.9227 g/cm3 to 10.2 cP and 0.9044 g/cm3 respectively, compared to those of the base vegetable oil. The objective of this study was the synthesis and characterization of biodiesel using commercial ionic liquid and its chloride modification. The ionic liquid catalysts were characterized using FTIR, Raman spectroscopy, DSC, TG and UV.